Analysing Organisations - Dawson, Sandra. author. aut Link
XXV, 269 p.
Keywords: For students who need to improve their understanding of organizations and the people in them. It is also relevant to those who are beginning a specialist study of organizations, particularly as it helps to bridge the gap between theory and practice. It is fully revised and updated.